Fertilization the Omission One Test as Determination Limiting Factors for Maize Biomass (Zea mays L.) - Koko Tampubolon; Bagus Fitra Azmi; Perdana Andriano Tamba; Ayu Widya Lestari; Kamaruddin Kamaruddin; Eka Lestari; Tommy Suranta Ginting (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2021)
Introduction: The research was aimed to obtain information on the impact of omission one test fertilization as a determination limiting factors for the growth and biomass of maize in variety Bonanza F1. Materials and Methods: The research was located in the experimental field, Faculty of Agriculture and Animal Husbandry, Universitas Tjut Nyak Dhien, Medan from December 2020 until February 2021. The research was applied by Randomized Block Design in non-factorial through fertilization of omission one test that has been converted (urea : SP-36 : KCl = 0.75 : 0.50 : 0.125 g polybag-1). The treatment of this research include P0 = non-fertilization; P1= N+P+K; P2= P+K; P3= N+K; P4= N+P using three replications. The parameters include plant height, leaf growth, total fresh weight, total dry weight, and the percentage of relative yield then processed using ANOVA and continued with DMRT at 5% ± standard error with SPSS v.20 software. Results: Informed that the omission one test technique significantly improved all the characteristics of maize in the variety Bonanza F1. The highest increase in plant height was found in the N+P of 83.65%, meanwhile, the highest leaf and biomass growth characters were found in N+P+K, ranged of 50.00 to 177.81% and 487.60 to 507.37%, respectively. It was obtained that the limiting factor for the maize growth in variety Bonanza F1 was found in the un-fertilization of nitrogen.